Caracterización reológica y determinación del perfil de textura del tofu - Espinoza Sanchez, Sergio Andre (2013)
In this work the study and characterization of the textura! properties of tofu prepared in the region San Martin , the general objective was the characterization and profiling of tofu texture was performed , the equipment used for the experiments was the texturometer STENTOR RSIC 11 software and to obtain data. Finally for data analysis and statistical analysis the Origin 5.0 and Statistica 7.0 software were used respectively. The variables analyzed were: the type of coagulant, coagulant (%), pressing and pressing time, and the response variables were profile texture (adhesiveness, cohesiveness, elasticity, gumminess, hardness and chewiness), Test Relaxation ('t1 and 't2) and Breakpoint. The feedstock was soybean originating in the region of Aserradero, Bagua, Amazonas and coagulants used were magnesium chloride and calcium sulfate. The methods used in the analysis of Tofu soy were: to determine the texture profile STEFFE model was used (for the textura! properties) and to test the model of relaxation for generalized Maxwell viscoelastic salid used (to calculate the influence of the variables in the viscoelastic property of Tofu). The results showed in the tofu texture profile in adhesiveness not influence any variable influence on the cohesiveness coagulant concentration (%) and the pressure in the hardness influence the type and concentration (%) of the coagulant, in influenced elasticity coagulant concentration (%) and the pressure in gumminess influence the type and the concentration (%) of the coagulant, eventually influenced chewiness in the type and concentration (%) of the coagulant. Relaxation In testing for the value of 't1 goal coagulant concentration (%) which influenced and 't2 was the pressing time which had the greatest influence. In the breaking point were the variables that influenced the type and concentration (%) of the coagulant.